A Diphenylalanine Based Pentapeptide with Fibrillating Self-Assembling Properties - Stefania-Claudia Jitaru; Andrei Neamtu; Gabi Drochioiu; Laura Darie-Ion; Iuliana Stoica; Brindusa-Alina Petre; Vasile-Robert Gradinaru (MDPI AG, 2023)
Peptides and their related compounds can self-assemble into diverse nanostructures of different shapes and sizes in response to various stimuli such as pH, temperature or ionic strength. Here we report the synthesis and characterization of a lysozyme derived pentapeptide and its ability to build well-defined fibrillar structures. Lysozyme FESNF peptide fragment was synthesized by solid phase peptide synthesis using the Fmoc/t-Bu strategy, purified by analytical high-performance liquid chromatography (HPLC) and its molecular weight was confirmed by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). Spectroscopic features of this pentapeptide were investigated by UV-visible spectroscopy and fluorimetry showing the pattern of marginal phenylalanine residues within the peptide sequence. Self-assembling properties were determined using atomic force microscopy (AFM), aggregation index and thioflavin T assay (ThT). FESNF generating fibrillar structures observed by AFM and aggregation propensity were primarily influenced by pH conditions. Moreover, the experimental data were confirmed by molecular dynamics simulation studies. The obtained fibrils will be used next to explore their potential to act as support material for medical and cosmetic application.